Analysis and synthesis of singular systems with time-delays - Wu, Zheng-Guang (Lecture notes in control and information sciences, 2013)
Singular time-delay systems are very suitable to describe a lot of practical systems such as manufacturing systems, networked control systems, power systems and electrical circuits. Thus, the past two decades have witnessed a significant progress on the theory of singular time-delay systems, and many fundamental and important topics have been successfully investigated including stability analysis, stabilization, guaranteed cost control, filtering, observer design, sliding mode control and so on. The main objective of this book is to present the latest developments and references in the analysis and synthesis of singular time-delay systems with or without Markov jumping parameters in a unified framework. The materials adopted in this book are mainly based on research results of the authors. This book will be of interest to academic researchers working in singular systems, time-delay systems and Markov jump systems and to graduate students interested in systems and control theory.